2010
DOI: 10.1108/17538391011072417
|View full text |Cite
|
Sign up to set email alerts
|

Exploring corporate social responsibility disclosure: the case of Islamic banks

Abstract: PurposeThe purpose of this paper is to explore whether any discrepancy exists between the corporate social activities disclosed in the annual reports of Islamic banks and the corporate social responsibility (CSR) disclosure index which has been developed based on the Islamic business ethics framework.Design/methodology/approachThis paper reports on a survey of annual reports of seven Islamic banks using the method of content analysis to measure the volume of CSR disclosure.FindingsThe results show the overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
233
1
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(259 citation statements)
references
References 31 publications
11
233
1
14
Order By: Relevance
“…Based on our study ISR index scores show that the extent of disclosure is 26% that is out of our expectations. Our results are consistent with [10] and [24] who found a gap between expectations and actual disclosure of CSR and conclude that CSRD for IBs is very low. Our finding also shows that there are differences between two countries and it concludes that the rules and pressure from government have impact on the information disclosed by Islamic banks.…”
Section: Research Limitations/implicationssupporting
confidence: 82%
See 2 more Smart Citations
“…Based on our study ISR index scores show that the extent of disclosure is 26% that is out of our expectations. Our results are consistent with [10] and [24] who found a gap between expectations and actual disclosure of CSR and conclude that CSRD for IBs is very low. Our finding also shows that there are differences between two countries and it concludes that the rules and pressure from government have impact on the information disclosed by Islamic banks.…”
Section: Research Limitations/implicationssupporting
confidence: 82%
“…They found that level of social disclosure by IBs is far from their expectation (13.3%). [24] using content analysis in analyze annual reports of seven IBs and found that level of CSRD for their sample is thirty-eighth. That is comparatively low comparing with their expectations, objective, and values of IBs.…”
Section: Stakeholder Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Research and development. Hasan and Harahap (2010) also argue that Islamic banks should disclose all the above mentioned information under the CSR disclosure policies to facilitate users' evaluation and assessment of the financial position and performance of an Islamic bank. In fact, Islamic banks should be proactive in disclosing information that would enable users to make an economic decision from their accounting reports.…”
Section: Gjat | January 2018 | Special Issue | 45 Issn : 2232-0474 | mentioning
confidence: 99%
“…These features encompass underlying philosophy and values, provision of interest-free products and services, restriction to Islamic acceptable deals, focus on development and social goals, and subjection to additional reviews by the SSB. Hasan and Harahap (2010), who adopt Haniffa and Hudaib's (2007) research framework, examine the CSR disclosure of Islamic banks based on eight dimensions, as below:…”
Section: Gjat | January 2018 | Special Issue | 45 Issn : 2232-0474 | mentioning
confidence: 99%